Metabolic and performance effects of Ilex paraguariensis (Yerbamate) during submaximal exercise and laboratory-based time trials in well-trained cyclists - Areta, J. L.; Austarheim, I.; Wagnesteen, H.; Capelli, C. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Ilex paraguariensis (IP) is a plant rich in polyphenols, saponins and xanthines consumed in beverages by millions of people world-wide, but its metabolic effects remain unknown. Traditionally IP has been considered a stimulant and recent research suggests that it increases fat oxidation during exercise. Our aim was to test the effect of IP on substrate utilisation during submaximal exercise and endurance performance in athletes.